2021
DOI: 10.1016/j.mcpro.2021.100079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Refinement of Sample Preparation Methods for Extracellular Matrix Proteome Coverage

Abstract: The extracellular matrix is a key component of tissues, yet it is underrepresented in proteomic datasets. Identification and evaluation of proteins in the extracellular matrix (ECM) has proved challenging due to the insolubility of many ECM proteins in traditional protein extraction buffers. Here we separate the decellularization and ECM extraction steps of several prominent methods for evaluation under real-world conditions. The results are used to optimize a two-fraction ECM extraction method. Approximately … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…This may lead to the decreased proportion of collagen in the analytical sample from the distal side of PDL. To overcome technical limitations attributable to the insolubility of the ECM, several ECM-enrichment protocols including decellularization, deglycosylation, and chemical digestion have been developed ( de Castro Bras et al, 2013 ; McCabe et al, 2021 ). Although these methods were shown to effectively enrich the core matrisome proteins, they also present a significant loss in the number of detected matrisome-associated proteins ( Krasny and Huang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to the decreased proportion of collagen in the analytical sample from the distal side of PDL. To overcome technical limitations attributable to the insolubility of the ECM, several ECM-enrichment protocols including decellularization, deglycosylation, and chemical digestion have been developed ( de Castro Bras et al, 2013 ; McCabe et al, 2021 ). Although these methods were shown to effectively enrich the core matrisome proteins, they also present a significant loss in the number of detected matrisome-associated proteins ( Krasny and Huang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…2). A recent study actually suggested that this method leads to high losses of matrisome components in the various extraction buffers when applied to a whole mouse powder [37].…”
Section: The Number Of Matrisome Proteins Identified In Mouse Skin Is Strongly Increased By Enrichment Methodsmentioning
confidence: 99%
“…It should also be noted here that a possible optimization applicable to all methods, especially if accurate quantification of proteoglycans and glycoproteins is desired, would be to combine several deglycosylation enzymes (in addition to the classical PNGaseF) to remove glycosaminoglycan (GAG) chains and other O-glycosylations, as described by others [32]. However, the systematic integration of a GAG removal step in ECM-centered analyses must be validated first as a recent study [37] suggested that it may decrease the number of PSMs for collagens and glycoproteins.…”
Section: The Matrisome Of Healthy Adult Mouse Skin Comprises 95 Core Matrisome Proteins and 141 Associated Matrisome Proteinsmentioning
confidence: 99%
“…Recently, proteomic analysis has been highlighted because of its complementary strategy, providing both compositional and quantitative data. It also allows an in-depth study of enriched proteins such as growth factors and cytokines in dECM [68]. In addition, as well as the development of analysis tools, the process of decellularization should be also optimized in order to qualify the dECM components.…”
Section: Compositional Quantification Of Decmmentioning
confidence: 99%